The perception about violence of the elderly admitted to asylum - Maxwell Macedo Isidoro, Miguir Terezinha Vieccelli Donoso, Salete Maria de Fátima Silqueira, Eline Lima Borges (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i2.3007